Determination of Entrepreneurship Education, Family Environment, and Self-Efficacy on Entrepreneurship Interest - Ida Ayu Putu Widani Sugianingrat; Ida I Dewa Ayu Yayati Wilyadewi; I Wayan Gde Sarmawa (Jurnal Economia, 2020)
Abstract: This study aims to study the effect of entrepreneurship education, work environment, and self-efficacy on student interest in entrepreneurship. This research was conducted on students of the Faculty of Economics, Hindu University of Indonesia in 2016 who were taking entrepreneurship courses totaling 270 students. The number of samples is determined based on the Slovin formula with an error of 10%. Based on these calculations, a total sample of 79 students was obtained. Determining students who become samples is done randomly. Data collection is done by conducting interviews directly with respondents, based on a pre-arranged questionnaire. The collected data is then tabulated, then processed using the SmartPLS 3.0 program. The results of the hypothesis testing show that entrepreneurship education and family environments have a significant positive effect on students' interest in entrepreneurship. Meanwhile, self-efficacy shows positive results but does not significantly influence the interests of students to become entrepreneurs.Keywords: entrepreneurship education, family environment, self-efficacy, entrepreneurial interest  Pengaruh Pendidikan Kewirausahaan, Lingkungan Kerja, dan Efikasi Diri terhadap Minat Mahasiswa Berwirausaha Abstrak: Penelitian ini bertujuan untuk melakukan kajian pengaruh pendidikan kewirausahaan, lingkungan kerja, dan efikasi diri terhadap minat mahasiswa untuk berwirausaha. Penelitian ini dilakukan pada mahasiswa Fakultas Ekonomi Universitas Hindu Indonesia angkatan tahun 2016 yang sedang mengambil mata kuliah kewirausahaan berjumlah 270 mahasiswa. Jumlah sampel penelitian ditentukan berdasarkan rumus Slovin dengan error 10%. Berdasarkan perhitungan tersebut diperoleh jumlah sampel sebanyak 79 mahasiswa. Penentuan mahasiswa yang menjadi sampel penelitian dilakukan secara acak. Pengumpulan data dilakukan dengan melakukan wawancara langsung kepada responden, berdasar pada kuesioner yang telah dipersiapkan. Data yang telah terkumpul selanjutnya dilakukan tabulasi, kemudian diolah dengan mempergunakan program SmartPLS 3.0. Hasil pengujian hipotesis menunjukkan pendidikan kewirausahaan dan lingkungan keluarga berpengaruh secara positif signifikan terhadap minat mahasiswa untuk berwirausaha. Sedangkan, efikasi diri menunjukkan hasil yang positif, tetapi tidak signifikan berpengaruh terhadap minat mahasiswa untuk berwirausaha. Kata Kunci: Pendidikan kewirausahaan, Lingkungan keluarga, Efikasi diri, Minat berwirausaha